Long-Term Survival and Quality of Life After Transfusion-Associated Pulmonary Edema in Critically III Medical Patients - Li, Guangxi (American College of Chest Physicians, 2010)
BACKGROUND: Transfusion-related acute lung injury (TRALI) and transfusion-associated circulatory overload (TACO) commonly complicate transfusion in critically ill patients. Prior outcome studies of TACO and TRALI have focused on short-term morbidity and mortality, but the long-term survival and quality of life (QOL) of these patients remain unknown. METHODS: In a nested case-control study, we compared survival and QOL between critically ill medical patients who developed pulmonary edema after transfusion (TRALI or TACO) and medical critically ill transfused controls, matched by age, gender, and admission diagnostic group. QOL in survivors was assessed with a 36-item short form health survey 1 year after initial hospitalization. RESULTS: Hospital, 1-year, and 2-year mortality among the 74 TRALI cases and 74 matched controls were 43.2% vs 24.3% (P = .020), 63.8% vs 46.4% (P = .037) and 74.3% vs 54.3% (P = .031), whereas among the 51 TACO cases and 51 matched controls these values were 7.8% vs 11.8% (P = .727), 38.0% vs 28.0% (P = .371), and 44.9% vs 38.8% (P = .512). When adjusted for age and baseline severity of illness in a Cox proportional hazard analysis, the development of TRALI remained associated with decreased survival (hazard ratio 1.86; 95% CI, 1.19-2.93; P = .006). Both TRALI (P = .006, P = .03) and TACO (P = .03, P = .049) were associated with prolonged ICU and hospital lengths of stay. CONCLUSIONS: In critically ill medical patients, development of TRALI, but not TACO, is independently associated with decreased long-term survival.